Annual reports in medicinal chemistry - Bristol, James A., 1946-; American Chemical Society Division of Medicinal Chemistry (San Diago : Academic Press, 1997)
Annual Reports in Medicinal Chemistry provides timely and critical reviews of important topics in medicinal chemistry together with an emphasis on emerging topics in the biological sciences, which are expectedto provide the basis for entirely new future therapies.
Includes bibliographical references and index.
Keywords: Pharmaceutical chemistry -- Periodicals; Clinical chemistry -- Periodicals